Afraid: Three Novels - Retribution, Ghosts & Alone - Jackson, Lisa; Ivy, Alexandra; Childs, Lisa; Childs, Lisa; Jackson, Lisa.; Ivy, Alexandra; Childs, Lisa. (New York, NY : Zebra Books/Kensington Publishing Corp., 2022)
A trio of never-before-released, linked novellas about dark secrets and revenge, all connected by St. Cecilias School for Girls. An elite boarding school and a haven for the daughters of the rich and famous, its a place where scandals are buried and secrets hidden. But for three former students, evil is about to resurface...
Lisa Childs.
Keywords: Girls schools -- Fiction; Life change events -- Fiction; Women -- Fiction; Revenge -- Fiction; Secrecy -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Romance fiction; Novellas